Optimization of Kieldahl digestion procedure for determination of mercury in lipstick by Box-Hunter design - Nguyen , Ngoc Hung; Huynh , Thi Nhan; Bui , Phuoc Hung; Nguyen , Thi Tuyet Nhung; Phan , Thi Hoang Yen (Tạp chí Khoa học Trường Đại học Sư phạm Thành phố Hồ Chí Minh, 2019)
This article describes the application of response surface methodology to the development of a procedure for mercury determination by cold vapor atomic absorption spectroscopy (CV-AAS) in lipstick samples after digestion by Kieldahl method. A Box-Hunter matrix was used to find optimal conditions for the procedure through a response surface study. Three variables “time, temperature, volume of HNO3 acid” were regarded as factors in the optimization study. In optimized condition, the linearity range was 0.2 ÷ 15 µg/L while the limit of detection (LOD) and limit of quantification (LOQ) were 0.17 and 0.57 ppb, respectively. This method presented good precision (RSD ≤ 8.2%) and good recovery (81%-109%). This method was applied to determine mercury in seven lipstick samples and the highest mercury content was 0.229 ± 0.016 mg/kg.